A Quarter-Century After Primary Direct Arterial Switch Operation: Four-D-Flow MRI Video Imaging of Blood Flow Dynamics Outcomes. (September 2017) - Sievers, Hans-Hinrich; Gabbert, Dominik; Rickers, Carsten
Four-dimensional (4-D) flow magnetic resonance imaging (MRI) examination was performed 25 years after a neonatal direct arterial switch operation for simple transposition of the great arteries. The 4-D flow MRI video shows physiological spiral anatomical configuration and laminar streamlines in the great arteries.